EEG biomarkers differentiate Lewy body dementia from Alzheimer's disease. (31st December 2021) - Meghdadi, Amir H.; Karic, Marija Stevanovic; Richard, Christian; Waninger, Shani; Mcconnell, Marissa; Poole, Jared; Rupp, Greg; Hamilton, Joanne M.; Boeve, Bradley F.; St. Louis, Erik K.; Berka, Chris
Abstract: Background: Resting state electroencephalography (rsEEG) is a neurophysiologic Alzheimer disease (AD) and alpha‐synucleinopathy (dementia with Lewy body (DLB) and Parkinson disease (PDD)) biomarker [1]–[5]. Background slowing (increased low frequency power, dominant rhythm (DR) slowing) is frequent in AD and DLB, more so in DLB. We sought to identify distinguishing rsEEG signatures between DLB and AD. Method: Participants included dementia patients [AD (n=26), DLB (n=12), PD (PDD; n=5)] and controls (HC; n=56). 20‐channel rsEEG was collected in eyes‐closed/eyes‐open conditions (5‐min each). Power spectral densities and coherences were measured using established methods [6]. Individual rsEEG power (delta, 1‐3 Hz; theta, 3‐7 Hz; alpha, 8‐13 Hz), theta/alpha ratio (TAR), dominant rhythm (DR), and DR frequency domain prominence were measured and averaged across groups, and effect sizes were determined and compared using Hedges g. Result: AD, DLB, and PDD groups exhibited increased low frequency (delta‐theta, 1‐5 Hz) power and TAR compared to controls (p<4x10 ‐4 ), with higher effect sizes in the DLB and PDD groups compared to AD. DR frequency was also decreased in all patient groups (DLB>PDD>AD) compared to controls (p=3x10 ‐9, p=3x10 ‐5, p=4x10 ‐4 ). AD alpha power and DR frequency domain prominence were reduced compared to controls and PDD/DLB groups (p<0.003). Both AD patients and controls had comparable posterior power distribution predominance of DR, while DLB power of DR was more anteriorly distributed. Compared to controls, delta coherence was higher in AD, but lower in DLB. Delta power was positively correlated with cognitive fluctuation (CAF) in DLB (r(8)=+0.67, p=0.03), while negatively correlated with MMSE in AD (r(24)=‐0.64, p=10 ‐5 ). Conclusion: DLB and AD had both common and distinct rsEEG signatures. Both had DR slowing and background slowing that was more severe in DLB than AD. Distinctive DLB findings included reduced posterior DR spatial dominance and decreased delta coherence. Conversely, distinct AD features were increased delta coherence, decreased alpha power, and decreased DR frequency prominence. Finally, the DLB and PDD groups had a similar magnitude of DR slowing, consistent with posteriorly dominant functional impairment in synucleinopathy reflected by corresponding regional rsEEG slowing, although future longitudinal prospective sequential rsEEG analyses are necessary to confirm these findings.